Two approaches to biological decontamination of groundwater and soil polluted by aromatics-characterization of microbial populations - Demnerová, Kateřina; Macková, Martina; Spěváková, Veronika; Beranová, K; Kochánková, Lucie; Lovecká, Petra; Ryslavá, Edita; Macek, Tomáš (International microbiology, 2005)
As part of the EU project MULTIBARRIERS, six new endogenous aerobic bacterial isolates able to grow in the presence of BTmX (benzene, toluene, m-xylene) were characterized with respect to their growth specificities. Preliminary analysis included restriction fragment length polymorphism profiles and 16S rDNA sequencing. The diversity of these strains was confirmed by denaturing gradient gel electrophoresis. Additional aerobic bacterial strains were isolated from the rhizospheres of plants grown in polychlorinated biphenyl (PCB)-contaminated soils. Pot experiments were designed to show the beneficial effect of plants on the bacterial degradation of PCBs. The effect of PCB removal from soil was evaluated and bacteria isolated from three different plant species were examined for the presence of the bph operon.
Keywords: chemické látky znečišťující vodu; biodegradace; financování organizované; Actinobacteria; Soil Microbiology; aromatické uhlovodíky; Plant Roots; Soil Pollutants; dekontaminace; Financing, Organized; látky znečišťující půdu; půdní mikrobiologie; rostliny; Biodegradation, Environmental; ekosystém; Plants; Ecosystem; kořeny rostlin; Hydrocarbons, Aromatic; Proteobacteria; Decontamination; Water Pollutants, Chemical